Comparative Study of Single versus Double Burr Hole Drainage for Chronic Subdural Hematoma - KC, Bidur; Shakya, Bikram; Thapa, Amit (Journal of College of Medical Sciences-Nepal, 2022)
Introduction: Various surgical technique is used for evacuation of chronic subdural hematoma. Burr hole drainage is a most preferred. However, there exist a controversy regarding single versus double burr hole among neurosurgeon. This study aims to compare the single versus double burr hole drainage for chronic subdural hematoma in terms of mortality, wound infection and recurrence. Methods: A retrospective observational study was performed over the period of 3 years. Data were collected in terms age, gender, type of surgery, mortality, wound infection and recurrence. These data were analysed to compare between the single versus double burr hole groups. Results: A total of 53 patients with chronic subdural hematoma underwent burr hole drainage were enrolled. Mean age of patients was 61.87 ± 17.35 years with male to female ratio 4.88:1. In this study, single burr hole was performed in 35 patients (66%) versus double burr hole in 18 patients (34%). Superficial surgical site infection was observed in 3 patients (5.7%) wherein 1 from single burr hole and 2 from double burr hole group with no statistically significant association (P value = 0.26). There was only 1 recurrence (1.9%). This was from single burr hole group versus no recurrence from double burr hole group which was not statistically significant (P value = 1.00). There was no mortality in both the groups in this study. Conclusions: There is no effect on mortality, infection and recurrence comparing single versus double burr hole drainage following evacuation of chronic subdural hematoma. Keywords: burr hole drainage; chronic subdural hematoma; recurrence.